Uji potensi ekstrak etanol daun nimba (Azadiractha indica) sebagai bahan pengawet pada ikan tongkol (Auxis thazard) - Ade Lestrari Rambu Leba; Nemay A. Ndaong; Maria AEGA Gelolodo (Jurnal Veteriner Nusantara, 2019)
This study aimed to the capability of the ethanol leaf extract obtained from neem (Azadiractha indica) as preservatives for frigate mackerel (Auxis thazard). Analysis was carried out by looking at the storability of the fish with two parameters, which are pH and total plate count (TPC). The samples were treated with different treatments by using different extract concentrations. This study was an experimental laboratory research using completely randomized design method with three replications of factorial 5x4. There were 5 treatments, 10% formalin (positive control), ice (negative control), 5% concentration of ethanol extract of neem leaves (K1), 10% concentration of ethanol extract of neem leaves (K2), 15% concentration of ethanol extract of neem leaves (K3). The mackerel were soaked for two hours, then stored at room temperature. The measurement of pH and TPC were done at 0 hour, 2 hours, 7 hours, and 12 hours. The result of this study showed that pH and TPC values gradually increased along with the length of time of observation. The ethanol leaf extract of neem (Azadiractha indica) as preservatives on the mackerel had storability for 2-7 hours. It can be concluded that the higher concentration of ethanol leaf extract of neem, the higher inhibitory effect on bacterial growth will be.